All‐Dielectric Metasurfaces for Simultaneous Giant Circular Asymmetric Transmission and Wavefront Shaping Based on Asymmetric Photonic Spin–Orbit Interactions. (23rd October 2017) - Zhang, Fei; Pu, Mingbo; Li, Xiong; Gao, Ping; Ma, Xiaoliang; Luo, Jun; Yu, Honglin; Luo, Xiangang
Abstract: The control of polarization and wavefront plays an important role in many optical systems. In this work, a monolayer metasurface is proposed to simultaneously realize circular asymmetric transmission (AT) and wavefront shaping based on asymmetric spin–orbit interactions. Circularly polarized incidence, accompanied with arbitrary wavefront modulation, experiences spin‐selected destructive or constructive interference. An extinction ratio of ≈10:1 and an AT parameter of ≈0.69 at 9.6 µm, as well as a full width half‐maximum of ≈2.9 µm (≈30% of the peak wavelength), are measured with the designed metasurface. These measured results are more than four times of those achieved with previous monolayer chiral structures. As far as it is known, this is the first report on the realization of simultaneous giant AT and arbitrary wavefront modulation with only one metasurface. Due to its fabrication simplicity and the multifunctionality of the designed metasurface, this work may provide a promising route to replace bulky cascading optical components with only one ultrathin metasurface for chiroptical spectroscopy, chiral imaging, optical communication, and so forth. Abstract : All‐dielectric metasurfaces, based on asymmetric spin–orbit interactions, are proposed to achieve giant and broadband circular asymmetric transmission, accomplished with spin‐selective wavefront shaping in transmission or reflection field. This work may have potential applications in the generation of complex optical fields and provide new ideas for studying chiral and functional materials.